The influence of promotion on consumer purchasing decisions to increase the income of paint shops in Medan - Manurung, Lambok; Ningsi, Etty Harya (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2024)
This research aims to assess the extent of the influence of Pro Ningsiotion on Consumer Purchase Decisions. The research design employed is quantitative explanatory research. The data processed were obtained from the distribution of questionnaires, and the data analysis technique used in this study is multiple linear regression. To explain the research description related to hypotheses, various analyses such as Validity Test, Reliability Test, and t-Test (Partial) were employed. Based on the results of the data analysis for the significance of the t-Test, it is indicated that the Promotion (X1) have a positive and significant influence on Consumer Purchase Decisions.